O impacto da COVID-19 no consumo e no modelo de negócio dos restaurantes de Porto Alegre - Baldissera, Izadora Petersohn (Universidade do Vale do Rio dos Sinos, 2020)
This article discusses the impacts of COVID-19, in the form of population consumption and the changes in business models in the restaurant sector in Porto Alegre, as a way to survive the economic crisis that currently affects all countries, through a exploratory and documentary study of a qualitative nature. The results demonstrate a repositioning in the restaurant business model, mainly with regard to the readjustment in the delivery format, as well as a new discourse with the client, based mainly on empathy and a greater presence on social networks, as a communication channel with the public.
Keywords: COVID-19; Consumo; Modelo de negócio; Restaurantes; Consumption; Business model; Restaurants